MRI for diagnosis of small bowel disease in paediatric crohns disease: a systematic review. (13th March 2011) - Giles, E; Barclay, A R; Chippington, S; Wilson, D C
Abstract : Introduction: Barium meal enteroclysis (BM) is the recommended imaging technique for small bowel inaccessable by ileocolonoscopy when diagnosing paediatric inflammatory bowel disease (IBD) (1). However it is subject to poor sensitivity and involves ionising radiation. MRI enterography (MRE) has recently been reported as an alternative methodology. We aimed to critically appraise the published evidence on use of MRE in diagnosis of paediatric IBD by systematic review. Methods: Review of all English language data reporting MRE for the investigation of patients <16 years with known or suspected IBD. Searches of Medline (January 1950–November 2010) and Pubmed (January 1950–November 2010) were performed using keyword and MeSH terms; IBD; MRI; small bowel imaging. Reference lists of potential studies, handsearching and personal collections of authors were also examined. Two authors independently assessed the quality of studies for inclusion using the QUADAS tool (2). A third author was an arbiter in cases of disagreement. Results: Database searches yielded 606 291 hits, combination word searches limited this to 968 titles. 38 studies were fully reviewed and 10 potential studies identified. 2 studies were excluded due to lack of separate paediatric data or inadequate methodological rigour. 8 studies were included (QUADAS scores 7–13/14) (table 1). Studies displayed heterogeneity in bowel preparation, scanning technique, reporting methodology and comparisons with BM, ultrasound and CT. Timing of ileocolonoscopy in relation to MRE was also variable. Two papers reported greater sensitivity and specificity for MRE in comparison to BM. Conclusion: MRE is an sensitive and specific tool for the diagnosis of paediatric IBD. However technical considerations require refinement and standardisation, however MRE offers a significant reduction in ionising radiation exposure. Current data suggest that MRE should supercede BM as the small bowel imaging technique in centres with appropriate expertise.